Ethnoscience Study: Chemistry Aspects of the Local Practice of Mango (Mangifera Indica L.) Fruit Ripening with Carbide for Contextualized Chemistry Learning - Ragadhita, Risti; Sriyati, Siti; Liliawati, Winny (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2025)
This study aims to explore the chemistry aspects of local practices on Mango (Mangifera indica L.)fruit ripening process with calcium carbide to be integrated in contextual chemistry learning.Literature studies from scientific journals related to natural and artificial fruit ripening werecomparatively analyzed in relation to local knowledge and scientific concepts to identify potentialintegration into science learning (especially chemistry). The results showed that the integration ofnatural science with local practices, such as fruit ripening, is an innovative way to teach chemicalkinetics in a contextualized way. The study of the fruit ripening process can help students understandchemical concepts, especially chemical kinetics, in a more relevant and practical context. Thus,chemistry learning is not only limited to theory and laboratory experiments, but also includes realapplications that are relevant to the lives of students and society.